Integrated Islamic Primary School In The Middle-Class Muslims Indonesia Conception - Suyatno Suyatno (Analisa: Journal of Social Science and Religion, 2015)
In the reform era, there are interesting developments regarding the trend of parental choice of education in Indonesia, when the Middle-class Muslim more interested send their children to schools based  on strong basic religious (Islamic). This study aims to answer the question why Islamic  Primary School attracted many parents of Middle-class Muslim? The method of data collection is done by indepth interviews, participant observation, and documentation. The results showed that the preferences of parents in educating their children in SDIT is influenced by the  three factors, namely; theological, sociological, and academic factors. Theological factors are reasons based on considerations of religion. Sociological factors associated with increasing image of Islamic schools. Academic factors related to the ability SDIT in achieving high academic achievement for their students. The position of the teacher as a murabby (moral guide) into the carrying capacity of the school principal. Murabby position makes the relationship between teacher and student is not merely a formal relationship in school, but as the relationship between parent and a child at home as well. Therefore, the future development of primary schools need to consider the quality of religious education in order to attract parental choice of education of the Middle-class Muslim.